2001
DOI: 10.1093/phr/116.5.474
|View full text |Cite
|
Sign up to set email alerts
|

Black-White Inequalities in Mortality and Life Expectancy, 1933–1999: Implications for Healthy People 2010

Abstract: The rationale that underlies the optimistic Healthy People 2010 forecasts, that future success can be built on a foundation of past success, is not supported when relative measures of inequality are used. There has been no sustained decrease in black-white inequalities in age-adjusted mortality or life expectancy at birth at the national level since 1945. Without fundamental changes, most probably related to the ways medical and public health practitioners are trained, evaluated, and compensated for prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(55 citation statements)
references
References 21 publications
(17 reference statements)
1
52
0
1
Order By: Relevance
“…Fourth, there are technical and conceptual limitations associated with examining race in epidemiologic analyses because it is complex and generally represents other economic, psychosocial, and environmental factors ( 17 – 19 ). Fifth, although whites were considered as the benchmark ( 20 ), or referent in this analysis, blacks had lower death rates for unintentional injury and suicide in some age groups and lower prevalences of binge drinking. Finally, differences within blacks and whites by sex, socioeconomic characteristics, and Hispanic subgroups were not considered, yet might modulate some of the relationships seen overall.…”
Section: Conclusion and Commentmentioning
confidence: 99%
“…Fourth, there are technical and conceptual limitations associated with examining race in epidemiologic analyses because it is complex and generally represents other economic, psychosocial, and environmental factors ( 17 – 19 ). Fifth, although whites were considered as the benchmark ( 20 ), or referent in this analysis, blacks had lower death rates for unintentional injury and suicide in some age groups and lower prevalences of binge drinking. Finally, differences within blacks and whites by sex, socioeconomic characteristics, and Hispanic subgroups were not considered, yet might modulate some of the relationships seen overall.…”
Section: Conclusion and Commentmentioning
confidence: 99%
“…4,10 There is a continuing disparity in mortality rates for heart, cerebrovascular, and renal diseases between blacks and whites in the United States. 11 More than two thirds of patients with stage 2 hypertension will require therapy with 2 or more drugs to achieve BP control, and those with lower BP goals (eg, patients with diabetes or renal disease) or higher elevations in BP may require 3 or more agents from different antihypertensive classes. 5 Combining agents from different antihypertensive classes targets multiple pathophysiologic mechanisms involved in BP elevations, which may lead to more effective BP lowering more promptly, at lower doses, and generally with fewer adverse events than with either component drug administered in high doses as monotherapy.…”
Section: Le Jacqmentioning
confidence: 99%
“…African Americans suffer from worse health outcomes across the lifespan, compared with their White counterparts, and this gap widens in older adulthood (Levine et al, 2001; Williams, 2005). Recent research has demonstrated that African Americans experience onset of disability at younger ages, on average, and that the cumulative effects of lifelong disparities in health and access to care account for much of this inequality (M.…”
mentioning
confidence: 99%